Fraude à execução na ação civil ex delicto - Galvão, Larissa Aveno Ordoñez de Andrade (2015)
This study results from a questioning involving two legal institutes, to wit: ex delicto civil claim and fraud committed against creditors during an execution suit, that is to say, in which moment one can declare the fraud committed during an execution suit when you have a connection between the civil scope and the criminal one (ex delicto civil claim)? Thus, this study is dedicated to the analysis of the ex delicto Civil Claim and its remediating action on damages arising out of fraudulent activity, the concept of damage per se and its classifications, its legal nature, its feasibility, its hybrid character in the context of legitimated criminal and civil law, the role of the Public Authorities towards the defenses of the individual´s interests without resources enough to enable one´s defense, its processing aspects, the effects resulting from decisions taken under criminal scope and likewise. Moreover, this study provides the analysis of the legal institute of fraud committed against creditors during an execution suit since the study of fraud in general, fraud against creditors, characteristics, requisites and the precedent conditions of a process, the interpleader´s figure and at last, a general overview on the New Civil Procedure Code concerning the legal institute of fraud committed against creditors during an execution suit. I did conclude that in spite of not being a process´ innovation, both doctrine and jurisprudence diverge on several issues as to the fraud institute, mainly on its configuring assumptions what makes its statement difficult when you have a multidisciplinary relationship between the civil and the criminal process, which is the case of the ex delicto civil claim analyzed hereby